Distinct Expression Patterns of Carbonic Anhydrase IX in Clear Cell, Microcystic, and Angiomatous Meningiomas. Issue 12 (12th September 2019) - Chkheidze, Rati; Cimino, Patrick J; Hatanpaa, Kimmo J; White, Charles L; Ferreira, Manuel; Piccirillo, Sara G M; Li, Li; Rajaram, Satwik; Nyagilo, James O; Burns, Dennis K; Raisanen, Jack M; Cai, Chunyu
Abstract: Clear cell, microcytic, and angiomatous meningiomas are 3 vasculature-rich variants with overlapping morphological features but different prognostic and treatment implications. Distinction between them is not always straightforward. We compared the expression patterns of the hypoxia marker carbonic anhydrase IX (CA-IX) in meningiomas with predominant clear cell (n = 15), microcystic (n = 9), or angiomatous (n = 11) morphologies, as well as 117 cases of other World Health Organization recognized histological meningioma variants. Immunostaining for SMARCE1 protein, whose loss-of-function has been associated with clear cell meningiomas, was performed on all clear cell meningiomas, and selected variants of meningiomas as controls. All clear cell meningiomas showed absence of CA-IX expression and loss of nuclear SMARCE1 expression. All microcystic and angiomatous meningiomas showed diffuse CA-IX immunoreactivity and retained nuclear SMARCE1 expression. In other meningioma variants, CA-IX was expressed in a hypoxia-restricted pattern and was highly associated with atypical features such as necrosis, small cell change, and focal clear cell change. In conclusion, CA-IX may serve as a useful diagnostic marker in differentiating clear cell, microcystic, and angiomatous meningiomas.